From data mining of chitinophaga sp. Genome to enzyme discovery of a hyperthermophilic metallocarboxypeptidase - Fernandes, Gabriela Cabral [UNESP]; Sierra, Elwi Guillermo Machado [UNESP]; Brear, Paul; Pereira, Mariana Rangel; Lemos, Eliana G. M. [UNESP] (MDPI, 2021)
For several centuries, microorganisms and enzymes have been used for many different applications. Although many enzymes with industrial applications have already been reported, different screening technologies, methods and approaches are constantly being developed in order to allow the identification of enzymes with even more interesting applications. In our work, we have performed data mining on the Chitinophaga sp. genome, a gram-negative bacterium isolated from a bacterial consortium of sugarcane bagasse isolated from an ethanol plant. The analysis of 8 Mb allowed the identification of the chtcp gene, previously annotated as putative Cht4039. The corresponding codified enzyme, denominated as ChtCP, showed the HEXXH conserved motif of family M32 from thermostable carboxypeptidases. After expression in E. coli, the recombinant enzyme was characterized biochemically. ChtCP showed the highest activity versus benziloxicarbonil Ala-Trp at pH 7.5, suggesting a preference for hydrophobic substrates. Surprisingly, the highest activity of ChtCP observed was between 55 °C and 75 °C, and 62% activity was still displayed at 100 °C. We observed that Ca2+, Ba2+, Mn2+ and Mg2+ ions had a positive effect on the activity of ChtCP, and an increase of 30 °C in the melting temperature was observed in the presence of Co2+. These features together with the structure of ChtCP at 1.2 Å highlight the relevance of ChtCP for further biotechnological applications.
Keywords: Chitinophaga sp; M32 family of peptidases; Metallocarboxypeptidase